Metal nanoparticles for cancer therapy: Precision targeting of DNA damage - Qian Chen; Chunyan Fang; Fan Xia; Qiyue Wang; Fangyuan Li; Daishun Ling (Elsevier, 2024)
Cancer, a complex and heterogeneous disease, arises from genomic instability. Currently, DNA damage-based cancer treatments, including radiotherapy and chemotherapy, are employed in clinical practice. However, the efficacy and safety of these therapies are constrained by various factors, limiting their ability to meet current clinical demands. Metal nanoparticles present promising avenues for enhancing each critical aspect of DNA damage-based cancer therapy. Their customizable physicochemical properties enable the development of targeted and personalized treatment platforms. In this review, we delve into the design principles and optimization strategies of metal nanoparticles. We shed light on the limitations of DNA damage-based therapy while highlighting the diverse strategies made possible by metal nanoparticles. These encompass targeted drug delivery, inhibition of DNA repair mechanisms, induction of cell death, and the cascading immune response. Moreover, we explore the pivotal role of physicochemical factors such as nanoparticle size, stimuli-responsiveness, and surface modification in shaping metal nanoparticle platforms. Finally, we present insights into the challenges and future directions of metal nanoparticles in advancing DNA damage-based cancer therapy, paving the way for novel treatment paradigms.